2004
DOI: 10.1590/s0103-64402004000100009
|View full text |Cite
|
Sign up to set email alerts
|

Cross-sectional evaluation of clinical parameters to select high prevalence populations for periodontal disease: the site comparative severity methodology

Abstract: Epidemiological studies have shown strong evidence that periodontal disease does not affect all subjects in the same manner. There are subjects and sites with higher risk for disease progression. This study tested parameters to select "a priori" sites and subjects potentially at risk. The data from periodontal clinical examinations of 2273 subjects was used. The clinical loss of attachment was measured in 6 sites per tooth. Using computer software, the patients were distributed into 14 age groups, with interva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 22 publications
2
9
0
Order By: Relevance
“…1). In the final screen, 24 studies were excluded (interreviewer agreement κ = 0.96) by full‐text evaluation and are described in Box 1 18‐41 …”
Section: Resultsmentioning
confidence: 99%
“…1). In the final screen, 24 studies were excluded (interreviewer agreement κ = 0.96) by full‐text evaluation and are described in Box 1 18‐41 …”
Section: Resultsmentioning
confidence: 99%
“…Therefore, epidemiological studies have used PAL as the principal measure of the chronic irreversible stage of this disease 13,16,22 . Conclusions from this study need to be interpreted with caution because of several methodological limitations.…”
Section: Variablesmentioning
confidence: 99%
“…In order to improve clinical management of periodontal patients, there is a need for the development of new diagnostic tests that can detect the presence of active disease, future disease progression, and evaluate the response to periodontal therapy. Advances in oral and periodontal diagnostic research are moving toward methods by which periodontal risk can be identified and quantified by objective measures such as biomarkers [6]. Biomarkers of disease play an important role in diagnosis, assessing the treatment outcomes, and drug discovery [7].…”
Section: Introductionmentioning
confidence: 99%